Führung von Patientinnen mit Augenerkrankungen während der Schwangerschaft: Diabetes, Glaukom, Uveitis - Mackensen, Friederike; Max, Regina (Der Ophthalmologe, 2012)
Many ocular diseases require treatment even during pregnancy. Some conditions, such as diabetic retinopathy tend to worsen during pregnancy but others, such as uveitis may benefit from the physiological changes occurring during pregnancy. But generally even a favorable development is not sufficient to obtain a steady state without treatment. Each medication applied during pregnancy should only be given after thorough consideration of the pros and cons and discussion of these with the patient. There are sufficient medications for ocular diseases that can be given when indicated following published guidelines and experiences. This review focuses on the course and therapy of glaucoma, diabetic retinopathy and uveitis during pregnancy.
Gesehen am 20.07.2018